2015
DOI: 10.1103/physreve.91.031001
|View full text |Cite
|
Sign up to set email alerts
|

Coriolis effects enhance lift on revolving wings

Abstract: At high angles of attack, an aircraft wing stalls. This dreaded event is characterized by the development of a leading edge vortex on the upper surface of the wing, followed by its shedding which causes a drastic drop in the aerodynamic lift. At similar angles of attack, the leading edge vortex on an insect wing or an autorotating seed membrane remains robustly attached, ensuring high sustained lift. What are the mechanisms responsible for both leading edge vortex attachment and high lift generation on revolvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 12 publications
5
26
0
Order By: Relevance
“…They concluded that, at low Ro , Coriolis forces stabilize the LEV and keep it attached. Recent numerical studies exploring the contributions of different fluid forces have supported their result [27]. …”
Section: Introductionmentioning
confidence: 88%
“…They concluded that, at low Ro , Coriolis forces stabilize the LEV and keep it attached. Recent numerical studies exploring the contributions of different fluid forces have supported their result [27]. …”
Section: Introductionmentioning
confidence: 88%
“…Quasi-steady aerodynamic models predict the time history of mid-stroke forces with remarkable accuracy [23] (figure 1d,e), a fact that is due to the peculiar stability of a flow structure known as the leading edge vortex (LEV), a region of high vorticity that forms on wings moving at high angles of attack [29,35,36]. Experiments with dynamically scaled robots [37 -39] and computational fluid dynamics (CFD) simulations [40] demonstrate that revolving wings create a stable LEV, and as a consequence, elevated force coefficients (figure 1e,f ). The stability (i.e.…”
Section: Hovering Flightmentioning
confidence: 99%
“…By contrast, a low aspect ratio wing rotating as a propeller has a Ro close to zero and the resulting LEV remains attached. CFD simulations of revolving wings in which the Coriolis term of the Navier-Stokes equation is removed predict rapid shedding of the LEV [40]. Fruit flies and other small hovering animals flap their wings with relatively high rotational velocity compared with their translational velocity [21], thus ensuring a low Ro number and large Coriolis effects.…”
Section: Hovering Flightmentioning
confidence: 99%
“…the rotation remains throughout the motion.This is divergent to the LEV that forms on a translating wing and pitching wing that is shed into the wake followed by periodic shedding [77]. The works of Lentik and Dickinson, and Jardin and David [49,40,41], suggest that the Coriolis acceleration that accompanies rotation plays a key role in the robust attachment of the LEV.…”
Section: Pitching Platesmentioning
confidence: 98%
“…The fluid dynamic field says that the prolonged attachment from a rotating wing is due to Coriolis accelerations. Jardine and David [41] have artificially tuned the Coriolis term in the Navier Stokes equation and showed that the LEV remained attached longer for a higher values. Eldredge and Jones [24] said the Coriolis is a a tilting term, which acts similar to tilting and stretching and then combine all three of the terms into a single term called Coriolis tilting term.…”
Section: Vorticity Flux Analysismentioning
confidence: 99%